The Creation of Entrepreneurship Class for Juvenile Resident: An Entrepreneurial Behavior Review for Residents of Penitentiary Class II Mojokerto - Wisnu Wardana, L; Handayati, P (KnE Social Sciences, 2018)
This study explains the creation of entrepreneurial behavior among the juvenile resident of the Penitentiary. This research is trying to provide an overview of the formation of entrepreneurial behavior of child prisoners, as well as supporting factors and inhibiting factors for the formation of entrepreneurial behavior of child prisoners. The basic assumption of personality-building activity is the process of behavior formation through the learning process. The targeted juveniles learn by sharpening knowledge, insight, and skills related to entrepreneurship through access to print media and electronic media, and also through the pursuit of business. Later, the targeted juveniles can become an entrepreneur who has good skill and moral. This study uses the formation of entrepreneurial behavior of the child prisoners through two coaching, that is, soft skill and hard skill and given to the child prisoners who numbered 45 people and become the citizen of LPP Class II Mojokerto. The type of research used is qualitative with case-study approach, where data acquisition is done through direct interview process with child prisoners. The result of this study confirms the previous findings that the learning outcomes of coaching are products and behavioral changes. This study proves that the behavioral changes are formed through the approach of entrepreneurial behavior, that is, discipline, responsibility, independence, curiosity, and creative. The findings indicate that changes in entrepreneurial behavior of child prisoners are strongly supported by factors of business-learning activities, trained instructors, motivation builders, good interaction, and entrepreneurial motivation. Conversely, the inhibiting factors are the boredom of the assisted people, the limited number of tools, the less extensive work space, the different character of the assisted juveniles and the limited capital to develop the business. Implications and ideas of future research are suggested. Further testing of this theory is needed to generalize results beyond this study. Keywords: behavior, entrepreneurship, prisoners